No means no! : teaching children about personal boundaries, respect and consent; empowering kids by respecting their choices and their right to say, 'no!' - Sanders, Jayneen (UpLoad Publishing Pty Ltd, 2015)
"'No Means No!' is a children's picture book about an empowered little girl who has a very strong and clear voice in all issues, especially those relating to her body and personal boundaries. This book can be read to children from 3 to 9 years. It is a springboard for discussions regarding children's choices and their rights. The 'Note to the Reader' at the beginning of the book and the 'Discussion Questions' on the final pages, guide and enhance this essential discussion. It is crucial that our children, from a very young age, are taught to have a clear, strong voice in regards to their rights - especially about their bodies. In this way, they will have the confidence to speak up when they are unhappy or feel uncomfortable in any situation. A strong, confident voice as a young child converts to a strong, confident pre-teen, teenager and adult. With the prevalence today of online and offline bullying and various forms of abuse, such as physical, emotional and sexual abuse; our young people need to learn (from a young age) to always speak up when their rights are not being respected"--Amazon website.